The influence of patriarchal cultural factors on pregnancy complications (antepartum hemorrhage) at Mitra Medika General Hospital, Bandar Klippa, Indonesia - Liyana Simamora; Zata Ismah; Susilawati (Majalah Obstetri dan Ginekologi, 2024)
HIGHLIGHTS